Significant modification of the surface morphology of polylactide (PLA) and PLA-halloysite nanocomposites in the presence of N,N’-ethylenebis(stearamide) upon thermal treatment - M. Pluta; J. Bojda; T. Makowski; E. Piorkowska; M. Murariu; L. Bonnaud; P. Dubois (eXPRESS Polymer Letters)
Surface morphology and bulk structure of polylactide (PLA) modified with halloysite nanotubes (HNT) treated with N,N’-ethylenebis(stearamide) (EBS) and untreated, as well as reference materials – PLA, EBS, and a blend of PLA with EBS, were examined. HNT is known to improve PLA properties, including mechanical and barrier properties. The materials were cold crystallized and tested using DSC, TGA, PLM, SALS, SEM, AFM. The additives affected nucleation and crystallization of PLA, but did not influence crystallinity, which was of approx. 37–40 %. In bulk, PLA crystallized in the form of spherulites in all materials. However, on surfaces of EBS-containing materials, a thin EBS layer with domain morphology was found. The EBS layer induced epitaxial crystallization of PLA in the form of parallel stacks of edge-on lamellae, the phenomenon reported for this polymer pair for the first time. It was observed in PLA with EBS modified HNT and in the PLA blend with EBS. Moreover, the EBS layers imparted hydrophobicity to the EBS-containing materials.